2000
DOI: 10.1128/mcb.20.6.1993-2003.2000
|View full text |Cite
|
Sign up to set email alerts
|

Loading of DNA-Binding Factors to an Erythroid Enhancer

Abstract: 3The HS-40 enhancer is the major cis-acting regulatory element responsible for the developmental stage-and erythroid lineage-specific expression of the human ␣-like globin genes, the embryonic and the adult ␣2/␣/1. A model has been proposed in which competitive factor binding at one of the HS-40 motifs, 3-NA, modulates the capability of HS-40 to activate the embryonic -globin promoter. Furthermore, this modulation was thought to be mediated through configurational changes of the HS-40 enhanceosome during devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 66 publications
0
15
0
1
Order By: Relevance
“…Plasmids-The reporter constructs pHS40-597GH, pHS40-␣590GH, and their mutated versions have been described previously (8,9). The constructions of pHS40-␣590Luc and pHS40-597Luc were done in the following way.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmids-The reporter constructs pHS40-597GH, pHS40-␣590GH, and their mutated versions have been described previously (8,9). The constructions of pHS40-␣590Luc and pHS40-597Luc were done in the following way.…”
Section: Methodsmentioning
confidence: 99%
“…Chromatin immunoprecipitation (ChIP) is a proven and useful approach to assess transcriptional regulation by NF-E2 and other factors in many contexts 40,41 and we used this method to determine if NF-E2 is recruited to any of its putative binding sites in the Rab27b locus. To establish specificity in this PCR-based assay, we first performed ChIP using dimethyl sulfoxide (DMSO)-treated murine erythroleukemia (MEL) cells, which activate NF-E2-dependent ␤-globin gene expression, and PCR primers specific for DNase I hypersensitive site 2 (HS2) within the ␤-globin locus control region.…”
Section: Mk Expression Of Rab27b Depends On the Transcription Factor mentioning
confidence: 99%
“…However, inasmuch as these studies were performed in 3T3 fibroblasts, it is possible that the results are more reflective of regulation in myofibroblasts than in SMCs. For this reason and because several studies have shown differences in transcriptional regulation between episomal reporter genes and chromosomal genes 17 and also because we 16 and others 18 have demonstrated that protein binding to oligonucleotide probes in EMSAs does not necessarily correlate with binding in vivo in the context of intact chromatin, we wanted to determine whether E2A proteins and SRF were specifically bound to the endogenous SM ␣-actin promoter in SMCs. We addressed this question using ChIP assays.…”
Section: E2a Proteins (E12/e47) and Srf Specifically Bound E-box-contmentioning
confidence: 99%